Novel active and passive anti-vibration mountings - Moshrefi-Torbati, M.; Forrester, J. A.; Forrester, A. I. J.; Keane, A. J.; Brennan, M. J. [UNESP]; Elliott, S. J. (Academic Press Ltd Elsevier B.V. Ltd, 2012)
This paper investigates a novel design approach for a vibration isolator for use in space structures. The approach used can particularly be applicable for aerospace structures that support high precision instrumentation such as satellite payloads. The isolator is a space-frame structure that is folded in on itself to act as a mechanical filter over a defined frequency range. The absence of viscoelastic elements in such a mounting makes the design suitable for use in a vacuum and in high temperature or harsh environments with no risk of drift in alignment of the structure. The design uses a genetic algorithm based geometric optimisation routine to maximise passive vibration isolation, and this is hybridised with a geometric feasibility search. To complement the passive isolation system, an active system is incorporated in the design to add damping. Experimental work to validate the feasibility of the approach is also presented, with the active/passive structure achieving transmissibility of about 19 dB over a range of 1-250 Hz. It is shown here that the use of these novel anti-vibration mountings has no or little consequent weight and cost penalties whilst maintaining their effectiveness with the vibration levels. The approach should pave the way for the design of anti-vibration mountings that can be used between most pieces of equipment and their supporting structure. Crown Copyright (C) 2011 Published by Elsevier Ltd. All rights reserved.